EVALUASI PELAKSANAAN PROGRAM PRAKTEK KERJA INDUSTRI PADA KOMPETENSI KEAHLIAN NAUTIKA KAPAL NIAGA - Evenda, Devi; Lapisa, Remon (Universitas Pendidikan Ganesha, 2020)
Problems in the implementation of apprenticeship students in the Nautika Kapal Niaga expertise in SMKN 2 Painan students include the difficulty of adjusting the apprenticeship schedule to the shipping industry, the lack of competence with student work opportunities has an impact on the low ability of students after implementing internship. Research methods are quantitative research methods and qualitative research methods whose use is adjusted to the desired data needs to answer research questions. Research respondents are each party involved in carrying out internship and 40 students. The instrument for qualitative research uses interview guidelines and specific observation guidelines for prakerin preparation data, while quantitative research data uses questionnaire instruments, learning outcomes tests and rubric of practical learning outcomes assessment. The results showed that 1) Formative evaluation related to the assessment of the implementation process of the apprenticeship in preparation of the apprenticeship had good results, the assessment of the implementation of teacher assignments (77%) was in the medium category and the industry supervisor (63%) was in the poor category, students' perceptions on the application of the teacher's tasks 69 % and industry advisers 66%, meaning that improvements still need to be done because they have moderate (sufficient) value. The results of the study on the assessment of the scope of work carried out by apprenticeship activities carried out by students 82% with good categories at stage I, 83% with good categories at stage II, 80% with good categories at stage III, 67% categorized as being at stage IV and 62% categorized poor in stage V, the overall average score is at an average of 74% in the medium category, 2) summative evaluation related to the assessment of the results of the perceived apprenticeship in the realm of attitude the overall average score in the learning outcomes of the realm of attitude is 72% in the medium category, the realm psychomotor practice 1 with an average of 80 and practice II with an average of 83, the value of good category and students declared competent in practice, in the cognitive realm obtained an average of 71.20 this score is still below the KKM in the cognitive domain that is 75, cognitive learning outcomes indicate that students' cognitive abilities still need to be improved.Keywords: Internship, Formative Evaluation, Summativ Evaluation